Penerapan Aplikasi Parental Control Screen Time dalam Penggunaan Smartphone bagi Anak-anak - Rudi Hermawan (Universitas Indraprasta PGRI Jakarta, 2019)
Smartphones today has become a necessity, including for children. Today, many children are used to using smartphones. Children often play games, watch youtube, enjoy chatting in social media and use Google for information search. This can be a good step so that children easily adapt to technology but can also have a negative impact. Parents must be vigilant if they see children often playing smartphones. It is important for parents to be able to control and supervise the use of children's smartphones. One solution is to use the Parental Control application. This smartphone child application can be set which applications are permitted and restrictions on playing time can be controlled. This is very good for healthy internet use among children. Screen Time is a parental control application that is useful for selecting, limiting, and supervising children's smartphone usage. This application has many features of control, supervision, scheduling and giving additional rewards for playing time if the child is doing a good assignment. By using these apps children can be set to play smartphones according to family need .